A surface-modified perovskite film and a method for preparing a solar cell
By using tripaniline to passivate the defects of the perovskite film, forming an ammonium salt passivation layer and enhancing charge transfer, the problem that the efficiency and stability of perovskite solar cells are affected by surface defects, and the effect of significantly improving photoelectric performance and stability is achieved.
Patent Information
- Application Number
- CN202210569911.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-23
- Filing Date
- 2022-05-24
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-05-24
AI Technical Summary
The efficiency and stability of perovskite solar cells are affected by surface defects. Although existing passivation materials can passivate defects, insulating materials affect charge transport.
Trianiline functionalized ammonium salt is used to passivate the lead site defect of the perovskite film, form an ammonium salt passivation layer, enhance charge transfer, and stabilize the perovskite phase through the hydrophobicity of the tripaniline functional group.
The photoelectric performance and stability of perovskite solar cells are significantly improved, the photoelectric conversion efficiency is improved by 10-30%, and non-radiative recombination losses are reduced.
Smart Images

Figure CN115084394B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells and relates to a perovskite modification method and a preparation process of a perovskite solar cell. Background Art
[0002] Perovskite solar cells have gained significant attention due to their advantages such as easy preparation, high efficiency and low cost. In just over a decade, their certified photoelectric conversion efficiency has increased from the initial 3.8% to 25.7%, with huge improvements in both device structure and photoelectric performance. Despite this, further efficiency improvement and battery stability are still the biggest problems facing this field. Among them, the factors that restrict the efficiency and stability of perovskites are the existence of defects. The defects on the surface of perovskites will become charge recombination centers, causing non-radiative recombination and affecting charge transfer. At the same time, the defects provide channels for moisture and oxygen in the air, destroying the phase stability of perovskites and restricting the commercial development of perovskite solar cells. One of the important methods to solve the surface defects of perovskite crystals is to passivate the surface defects of perovskites. There are a large number of charge traps on the grain boundaries or film surfaces of perovskites. These surface traps are mainly composed of uncoordinated ions Pb on the surface of the crystal. 2+ , I - Passivation refers to the use of certain chemicals to react with surface elements to inactivate their electronic or chemical activity. The perovskite surface is post-treated with phenylethylamine hydroiodide (PEAI). The surface passivated by heat treatment with PEAI forms a low-dimensional structure, while the passivated surface annealed at ambient temperature reduces the reaction of the perovskite surface with water and oxygen in the air through the passivation ability of PEAI itself, while reducing the Pb / I ratio to fill I - The vacancies generated by migration can improve the photoelectric efficiency and stability of the battery. However, most of the existing passivation materials are insulating materials. Although they can passivate the defects on the surface of perovskite, the insulating materials themselves still affect charge transfer. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the present invention provides a surface-modified perovskite film and a method for preparing a solar cell, the purpose of which is to use triphenylamine functionalized ammonium salt to passivate the defects of the perovskite film, inhibit non-radiative recombination, and enhance charge transfer. When used in a perovskite solar cell, it can effectively improve the photoelectric performance of the device and improve the stability of the perovskite solar cell.
[0004] The technical solution adopted by the present invention is:
[0005] A method for surface modification of a perovskite layer, wherein the perovskite layer is a layer of a perovskite solar cell, wherein the method uses triphenylamine functionalized ammonium salt to passivate lead site defects on the surface of the perovskite, thereby forming an ammonium salt passivation layer on the surface of the perovskite to obtain a surface modified perovskite layer:
[0006] The general structural formula of the triphenylamine functionalized ammonium salt is:
[0007]
[0008] Wherein: R1 and R2 are hydrogen, C1-C18 alkyl chain, hydroxyl, aldehyde, carboxyl, methylamino, dimethylamino, mercapto, sulfonic acid, -O-R6, -S-R7, R3, R4, R5, R6, R7 are selected from C1-C18 alkyl chains; X is any halogen; n is an integer of 1-12;
[0009] The structures available for triphenylamine functionalized ammonium salts are as follows:
[0010]
[0011]
[0012] The specific steps of the method are: spin coating a 1-5 mg / mL triphenylamine functionalized ammonium salt solution on the perovskite layer, and placing it at 20°C-100°C for 10-15 minutes to obtain the solution; the solvent used in the solution is isopropanol, chlorobenzene or ethyl acetate.
[0013] A method for preparing a perovskite solar cell, the perovskite solar cell comprising a transparent conductive substrate, an electron transport layer, a surface-modified perovskite layer, a hole transport layer, and a metal electrode, the surface-modified perovskite layer being prepared by the method of claim 1, and the specific steps are as follows:
[0014] (1) The transparent conductive substrate is ultrasonically cleaned in different solvents, and then the surface is cleaned by ultraviolet ozone; the conductive substrate is FTO conductive glass or ITO conductive glass.
[0015] (2) after step (1), preparing an electron transport layer on the transparent conductive substrate by thermal spraying or spin coating; the electron transport layer is titanium dioxide or tin dioxide;
[0016] (3) subjecting the conductive substrate coated with the electron transport layer to ultraviolet ozone surface treatment, and spin coating the perovskite precursor solution to prepare the perovskite film;
[0017] The perovskite film is Cs x (FA,MA) 1-x PbI 3-y Br y Or one of the all-inorganic perovskites CsPbI2Br and CsPbIBr2;
[0018] Among them, FA is CH(NH2)2 +, MA is CH3NH3 + , 0<x<0.1, 0<y<0.6;
[0019] (4) performing a triphenylamine functionalized ammonium salt passivation treatment on the perovskite film prepared in step (3);
[0020] (5) preparing a hole transport layer solution on the perovskite film passivated in step (4) by spin coating;
[0021] The hole transport layer solution comprises a hole transport material, an additive, and an organic solvent, wherein the hole transport material is Spiro-OMeTAD (i.e., 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene); the additive is LiTFSI (i.e., bis(trifluoromethane)sulfonyl imide, tert-butylpyridine, and FK209 Co(III)-TFSI (i.e., tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt tris(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide salt); and the organic solvent is chlorobenzene or acetonitrile;
[0022] (6) Depositing a metal electrode onto the hole transport layer by vacuum evaporation.
[0023] The perovskite film is Cs x (FA,MA) 1-x PbI 3-y Br y When the precursor solution is used, the molar ratio of lead iodide: methylammonium iodide: lead bromide: methylammonium bromide: cesium iodide is 1-1.5: 1-1.5: 0.1-0.2: 0.1-0.2: 0.05-0.1.
[0024] When the perovskite film is CsPbI2Br, the molar ratio of lead iodide: lead bromide: cesium iodide in its precursor solution is 1-2:1-2:2-4.
[0025] When the perovskite film is CsPbIBr2, the molar ratio of lead bromide to cesium iodide in its precursor solution is 1:1-2.
[0026] The method for passivating perovskite of the present invention is used to prepare perovskite solar cells.
[0027] The film in step (3) is Cs x (FA,MA) 1-x PbI 3-y Br y Or one of the all-inorganic perovskites CsPbI2Br and CsPbIBr2;
[0028] Among them, FA is CH(NH2)2 +, MA is CH3NH3 + , x is any value between 0 and 0.1, y is any value between 0 and 0.6;
[0029] (a) When the perovskite film is Cs x (FA,MA) 1-x PbI 3-y Br y The precursor solution preparation method is to dissolve lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI in a specific molar ratio in an organic solvent, and stir at 60°C;
[0030] (b) When the perovskite film is CsPbI2Br, the precursor solution is prepared by dissolving lead iodide PbI2, lead bromide PbBr2, and cesium iodide CsI in a specific molar ratio in an organic solvent, and stirring at 60°C;
[0031] (c) When the perovskite film is CsPbIBr2, the precursor solution is prepared by dissolving lead bromide PbBr2 and cesium iodide CsI in a specific molar ratio in an organic solvent and stirring at 60°C;
[0032] Wherein, the organic solvent is a mixed solvent of N,N-dimethylformamide DMF and dimethyl sulfoxide DMSO in a certain volume ratio.
[0033] In step (5), the hole transport layer solution comprises a hole transport material, an additive, and an organic solvent, wherein the hole transport material is Spiro-OMeTAD; the additive is LiTFSI, 4-tert-butylpyridine, and FK209 Co(III)-TFSI; and the organic solvent is chlorobenzene and acetonitrile;
[0034] The metal electrode described in step (6) is one of gold and silver.
[0035] The beneficial effects of the present invention are as follows: the triphenylamine functionalized ammonium salt modification layer can not only effectively passivate the lead site defects on the surface of the perovskite, but also enhance the extraction of charges and accelerate the transfer of charges. At the same time, the hydrophobicity of the triphenylamine functional group is used to stabilize the perovskite phase, thereby enhancing the stability of the device while improving the efficiency of the device. Compared with the unmodified perovskite solar cell, the photoelectric conversion efficiency has increased by more than 10-30%, which significantly improves the device efficiency. The spin coating of the triphenylamine functionalized modification layer is simple in process and easy to prepare, providing a path for the commercialization of perovskite solar cells. This method can effectively reduce the non-radiative recombination loss of the battery, obtain a stable and efficient perovskite solar cell, and provide a feasible strategy for the passivation of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1JV curve of organic-inorganic hybrid CsFAMA perovskite solar cell based on triphenylamine functionalized ammonium salt modification technology.
[0037] Figure 2 JV curve of pure inorganic CsPbI2Br perovskite solar cell based on triphenylamine functionalized ammonium salt modification technology.
[0038] Figure 3 JV curve of pure inorganic CsPbIBr2 perovskite solar cell based on triphenylamine functionalized ammonium salt modification technology.
[0039] Figure 4 This is the Pb 4f orbital X-ray photoelectron spectrum of the pure inorganic CsPbI2Br perovskite film based on triphenylamine functionalized ammonium salt modification technology.
[0040] Figure 5 This is the I 3d orbital X-ray photoelectron spectrum of the pure inorganic CsPbI2Br perovskite film and triphenylamine functionalized ammonium salt powder based on triphenylamine functionalized ammonium salt modification technology. DETAILED DESCRIPTION
[0041] The following specific embodiments and drawings are used to describe the preparation and application of the present invention in detail. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0042] Example 1
[0043] Organic-inorganic CsFAMA perovskite solar cell using triphenylamine functionalized ammonium salt (TPAI) as a modified layer and preparation method thereof:
[0044] The structure of the triphenylamine functionalized ammonium salt used is:
[0045]
[0046] The structure of the perovskite solar cell is:
[0047] FTO / c-TiO2 / m-TiO2 / Perovskite / TPAI / Spiro-OMeTAD / Au.
[0048] The preparation process of the perovskite solar cell is as follows:
[0049] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.
[0050] (2) Using the thermal spray method, a titanium isopropanol solution and an ethanol solution with a volume ratio of 1:9 were sprayed on the FTO and heated to 500°C for calcination. Then, commercial mesoporous TiO2 (30NRD) diluted with anhydrous ethanol in a volume ratio of 6:1 was rotated at 5000 rpm for 20 seconds to coat a 200 nm thick mesoporous TiO2 layer on the substrate. Then, the surface was treated with ozone UV for 20 minutes.
[0051] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 4:1) at a molar ratio of 1.30:1.19:0.14:0.14:0.07, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 15 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 120°C for 1 h.
[0052] (4) Then, 60 μL of 3 mg / mL TPAI solution was dropwise added onto the perovskite film by spin coating at 3000 rpm for 30 s.
[0053] (5) The hole transport layer solution (73 mg Spiro-OMeTAD, 30 μL tert-butylpyridine, 18 μL LiTFSI, 30 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film at a speed of 3000 rpm and a spin-coating time of 30 s. Finally, 100 nm of Au was deposited onto the device film by vacuum evaporation.
[0054] Comparative Example 1
[0055] Preparation method of CsFAMA-free perovskite solar cells:
[0056] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.
[0057] (2) Using the thermal spray method, a titanium isopropanol solution and an ethanol solution with a volume ratio of 1:9 were sprayed on the FTO and heated to 500°C for calcination. Then, commercial mesoporous TiO2 (30NRD) diluted with anhydrous ethanol in a volume ratio of 6:1 was rotated at 5000 rpm for 20 seconds to coat a 200 nm thick mesoporous TiO2 layer on the substrate; then the surface was treated with ozone UV for 20 minutes.
[0058] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 4:1) at a molar ratio of 1.30:1.19:0.14:0.14:0.07, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 15 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 120°C for 1 h.
[0059] (4) The hole transport layer solution (73 mg Spiro-OMeTAD, 30 μL tert-butylpyridine, 18 μL LiTFSI, 30 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film at a speed of 3000 rpm and a spin-coating time of 30 s. Finally, 100 nm of Au was deposited onto the device film by vacuum evaporation.
[0060] Figure 1 The JV curves of the unmodified perovskite solar cell modified with triphenylamine functionalized ammonium salt are compared. oc 1.08V, J sc 25.06mAcm -2 , FF is 0.70, PCE is 19.05%, and the photoelectric conversion efficiency V obtained by the perovskite solar cell based on TPAI modification technology in Example 1 is oc 1.14V, J sc 25.40 mA cm -2 , FF is 0.77, PCE is 22.23%; the PCE of the perovskite solar cells before and after modification increased from 19.05% to 22.23%, an overall increase of 16.7%, and the photoelectric conversion efficiency was significantly improved after modification.
[0061] Example 2
[0062] Pure inorganic CsPbI2Br perovskite solar cell using triphenylamine functionalized ammonium salt (TPAI) as a modified layer and preparation method thereof:
[0063] The structure of the triphenylamine functionalized ammonium salt used is:
[0064]
[0065] The structure of the perovskite solar cell is FTO / c-TiO2 / Perovskite / TPAI / Spiro-OMeTAD / Au.
[0066] The preparation process of the perovskite solar cell is as follows:
[0067] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.
[0068] (2) Using a thermal spray method, a titanium isopropanol solution and an ethanol solution with a volume ratio of 1:9 were sprayed onto FTO, heated and calcined at 500°C, and then subjected to ozone UV surface treatment for 20 minutes.
[0069] (3) Lead iodide PbI2, lead bromide PbBr2, and cesium iodide CsI were dissolved in a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio of 1:9) at a molar ratio of 1:1:2, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 1000 rpm for 10 s and 4000 rpm for 30 s. 15 s before the end of the program, 120 μL of isopropanol was dropped on the substrate and annealed at 280°C for 10 min.
[0070] (4) Then, 60 μL of 3 mg / mL TPAI solution was dropwise added onto the perovskite film by spin coating at 3000 rpm for 30 s.
[0071] (5) A hole transport layer solution (73 mg Spiro-OMeTAD, 30 μL tert-butylpyridine, 18 μL LiTFSI, 30 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.
[0072] Finally, 100 nm of Au was deposited onto the device film by vacuum evaporation.
[0073] Comparative Example 2
[0074] Preparation method of pure inorganic CsPbI2Br perovskite solar cell without modification layer
[0075] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.
[0076] (2) Using a thermal spray method, a titanium isopropanol solution and an ethanol solution with a volume ratio of 1:9 were sprayed onto FTO, heated and calcined at 500°C, and then subjected to ozone UV surface treatment for 20 minutes.
[0077] (3) Lead iodide PbI2, lead bromide PbBr2, and cesium iodide CsI were dissolved in a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio of 1:9) at a molar ratio of 1:1:2, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 1000 rpm for 10 s and 4000 rpm for 30 s. 15 s before the end of the program, 120 μL of isopropanol was dropped on the substrate and annealed at 280°C for 10 min.
[0078] (4) A hole transport layer solution (73 mg Spiro-OMeTAD, 30 μL tert-butylpyridine, 18 μL LiTFSI, 30 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.
[0079] Finally, 100 nm of Au was deposited onto the device film by vacuum evaporation.
[0080] Figure 2 The JV curves of the unmodified CsPbIBr2 perovskite solar cell modified with triphenylamine functionalized ammonium salt are compared. The photoelectric conversion efficiency of the unmodified CsPbIBr2 perovskite solar cell in Comparative Example 2 is: V oc 1.18V, J sc 15.70 mA cm -2 , FF is 0.67, PCE is 12.42%, and the photoelectric conversion efficiency of the perovskite solar cell based on TPAI modification technology in Example 2 is V oc 1.30V, J sc 16.09 mA cm -2 , FF is 0.78, PCE is 16.32%; the PCE of the perovskite solar cells before and after modification increased from 12.42% to 16.32%, an overall increase of 31.4%, with significant effects.
[0081] Example 3
[0082] Pure inorganic CsPbIBr2 perovskite solar cell using triphenylamine functionalized ammonium salt (TPAI) as a modified layer and preparation method thereof:
[0083] The structure of the triphenylamine functionalized ammonium salt used is:
[0084]
[0085] The structure of the perovskite solar cell is FTO / c-TiO2 / Perovskite / TPAI / Spiro-OMeTAD / Au.
[0086] The preparation process of the perovskite solar cell is as follows:
[0087] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.
[0088] (2) Using a thermal spray method, a titanium isopropanol solution and an ethanol solution with a volume ratio of 1:9 were sprayed onto FTO, heated and calcined at 500°C, and then subjected to ozone UV surface treatment for 20 minutes.
[0089] (3) Lead bromide PbBr2 and cesium iodide CsI were dissolved in an organic solvent of dimethyl sulfoxide in a molar ratio of 1:1 and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 1500 rpm for 15 s and 3500 rpm for 30 s, and annealed at 200°C for 10 min.
[0090] (4) Then, 60 μL of 3 mg / mL TPAI solution was dropwise added onto the perovskite film by spin coating at 3000 rpm for 30 s.
[0091] (5) A hole transport layer solution (73 mg Spiro-OMeTAD, 30 μL tert-butylpyridine, 18 μL LiTFSI, 30 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.
[0092] Finally, 100 nm of Au was deposited onto the device film by vacuum evaporation.
[0093] Comparative Example 3
[0094] Preparation method of pure inorganic CsPbIBr2 perovskite solar cell without modification layer:
[0095] The method adopts the preparation method of Example 3, except that step (4) of spin coating the TPAI solution is removed. The remaining steps are consistent with Example 3, and finally a pure inorganic CsPbIBr2 perovskite solar cell without a modification layer is obtained.
[0096] Figure 3 Comparison of JV curves of perovskite solar cells modified with triphenylamine functionalized ammonium salt and unmodified. The photoelectric conversion efficiency of the unmodified perovskite solar cell in Comparative Example 3 is V oc 1.23V, J sc 11.03 mA cm -2, FF is 0.67, PCE is 9.20%, and the photoelectric conversion efficiency of the perovskite solar cell based on TPAI modification technology in Example 3 is V oc 1.29V, J sc 12.05 mA cm -2 , FF is 0.76, and PCE is 11.88%. The PCE of the perovskite solar cell before and after modification increased from 9.20% to 11.88%, an overall increase of 29.1%, and the efficiency was significantly improved.
[0097] like Figure 4 As shown, the X-ray energy spectra of the Pb 4f orbitals of two perovskite films with and without TPAI show that when a layer of TPAI modification layer is added to the perovskite film, the zero-valent lead peak disappears significantly after modification, and the Pb4f peak of the modified film shifts toward the low energy band direction, indicating that the use of TPAI modification effectively suppresses Pb defects.
[0098] like Figure 5 As shown, the X-ray energy spectra of the I 3d orbitals of TPAI powder and two perovskite films with and without TPAI show that the I 3d peak of TPAI powder has a lower energy band than that of the two films, indicating that the iodine ions on the ammonium salt have a stronger coordination ability with the lead on the perovskite film, forming a Pb-I bond, which is more conducive to reducing defects on the perovskite film.
Claims
1. A method for surface modification of a perovskite layer, characterized in that: The perovskite layer is a layer of a perovskite solar cell. The method uses triphenylamine functionalized ammonium salt to passivate the lead site defects on the surface of the perovskite, forming an ammonium salt passivation layer on the surface of the perovskite to obtain a surface-modified perovskite layer: The general structural formula of the triphenylamine functionalized ammonium salt is: Wherein: R1 and R2 are hydrogen, C1-C18 alkyl chain, hydroxyl, aldehyde, carboxyl, methylamino, dimethylamino, mercapto, sulfonic acid, -O-R6, -S-R7, R3, R4, R5, R6, R7 are selected from C1-C18 alkyl chains; X is any halogen; n is an integer of 1-12; The specific steps of this method are: A 1-5 mg / mL triphenylamine functionalized ammonium salt solution is spin-coated on the perovskite layer and placed at 20° C.-100° C. for 10-15 minutes to obtain the perovskite layer; the solvent used in the solution is isopropanol, chlorobenzene or ethyl acetate.
2. A method for preparing a perovskite solar cell, wherein the perovskite solar cell comprises a transparent conductive substrate, an electron transport layer, a surface-modified perovskite layer, a hole transport layer, and a metal electrode, wherein the surface-modified perovskite layer is prepared by the method of claim 1, characterized in that: The specific steps are as follows: (1) ultrasonically cleaning the transparent conductive substrate in different solvents, followed by ultraviolet ozone surface cleaning; (2) after step (1), preparing an electron transport layer on the transparent conductive substrate by thermal spraying or spin coating; The electron transport layer is titanium dioxide or tin dioxide; (3) subjecting the conductive substrate coated with the electron transport layer to ultraviolet ozone surface treatment, and spin coating the perovskite precursor solution to prepare the perovskite film; The perovskite film is Cs x (FA,MA) 1-x PbI 3-y Br y Or one of the all-inorganic perovskites CsPbI2Br and CsPbIBr2; Among them, FA is CH(NH2)2 + , MA is CH3NH3 + , 0<x<0.1, 0<y<0.6; (4) performing a triphenylamine functionalized ammonium salt passivation treatment on the perovskite film prepared in step (3); (5) preparing a hole transport layer solution on the perovskite film passivated in step (4) by spin coating; The hole transport layer solution comprises a hole transport material, an additive, and an organic solvent, wherein the hole transport material is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene; the additive is bis(trifluoromethane)sulfonyl imide, 4-tert-butylpyridine and tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt tris(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide salt); and the organic solvent is chlorobenzene or acetonitrile; (6) Depositing a metal electrode onto the hole transport layer by vacuum evaporation.
3. A method for preparing a perovskite solar cell according to claim 2, characterized in that: The perovskite film is Cs x (FA,MA) 1-x PbI 3-y Br y When the precursor solution is used, the molar ratio of lead iodide: methylammonium iodide: lead bromide: methylammonium bromide: cesium iodide is 1-1.5: 1-1.5: 0.1-0.2: 0.1-0.2: 0.05-0.
1.
4. A method for preparing a perovskite solar cell according to claim 2, characterized in that: When the perovskite film is CsPbI2Br, the molar ratio of lead iodide: lead bromide: cesium iodide in its precursor solution is 1-2:1-2:2-4.
5. A method for preparing a perovskite solar cell according to claim 2, characterized in that: The perovskite film is CsPbIBr2, and the molar ratio of lead bromide to cesium iodide in its precursor solution is 1:1-2.
Citation Information
Patent Citations
A fully-inorganic perovskite-type solar cell and its preparation method
AU2020100802A4
Perovskite type solar cell based on cooperative post-processing of multiple ammonium salts and preparation method thereof
CN110993798A